Conditional Properties of Estimators of Repeated Measurements Model (Type I) - Hayder Abbood Kori; Abdulhussein Saber ALMouel (Genius Journals, 2021)
This paper studies the conditional biases and mean squared errors of the repeated measurements model for two types 1 and 2 estimators.
Keywords: Repeated Measurements Model; Type 1 Estimators; Type 2 Estimators